IMPROVING READING SKILL USING JIGSAW - Fadhil Muhammad Sopyan; Khoulah Uswatun Hasanah; Acep Haryudin (PROJECT (Professional Journal of English Education), 2019)
Abstract This study is aim to identify improving student’s reading skill using jigsaw. Whether jigsawcan improving students ability in reading skill. The research method used in this research is Qualitative Method and Classroom Action Research as a design.The subject of this study were 32 students of the tenth gradesin one of SMK in Bandung Barat. There were seven encounters covered on those two periods; three encounters were for tests, and the other four encounters were for doing treatment. The treatment was teaching reading skill, especially in reading Narrative text, with the used of Jigaw method.The instruments used in this research were observation, interview, field notes and tests. The tests were used to test the students on pre-test, post-test 1 and post-test 2. The tests given subsisted of 10 items in the form of find out the structure of Narrative text and Comprehenison questions based on the text. This research aims at improving reading ability by using jigsaw method in understanding generic structure, language feature and kinds of narrative text. Through two periods, three tests and four treatments, the teaching and learning process is done and run very well in the year of one SMK in Bandung. As shown in the data above that the increase in score almost reaching KKM is 6.5 while the specified KKM is 7.0. Keywords:Reading, Jigsaw, classroom action research